2013
DOI: 10.3329/cmoshmcj.v12i3.16707
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Post Obturation Pain Following Single Visit Root Canal Treatment

Abstract: Introduction: Root canal treatment (RCT) is a common procedure in dentistry. In recent year, single visit RCT has gained increased acceptance as a treatment procedure of RCT. One of the problem of RCT is post obturation pain. Objectives: This study was conducted to determine the incidence of post obturation pain related to single visit RCT in asymptomatic non-vital single rooted teeth. Methods: A total 60 cases of endodontically involved asymptomatic non-vital single rooted teeth without any evidence of periap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…57.3%. Similar results were shown by Jabeen et al 9 which documented that 53.3% were males. A study conducted by Elmubarak et al 3 showed female predominance i.e.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…57.3%. Similar results were shown by Jabeen et al 9 which documented that 53.3% were males. A study conducted by Elmubarak et al 3 showed female predominance i.e.…”
Section: Discussionsupporting
confidence: 90%
“…Some of the problems of RCT are post obturation pain, inter appointment pain and swelling. Post obturation pain is the pain of any degree after endodontic treatment 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the bar graph shows slightly more pain prevalence among female patients but this could be due to more number of female participants (64%) compared to males (34%) as shown in Figure D in this study. Other studies have shown pain to be more prevalent among females compared to males [20][21][22].These results could be due to higher number of sample size taken by these studies which our study lacked. While some studies show no relevant difference among male and females in experiencing pain and suggest large prospective studies with registry data including confounders to be done in the future [23,24].…”
Section: Discussionmentioning
confidence: 67%
“…Postoperative pain decreases as the periapical lesion volume sizes increase (29). This phenomenon might be explained with the presence of su cient space for pressure distribution in cases with large periapical lesions (34). However, are-ups develop less frequently in teeth without apical periodontitis (5).…”
Section: Discussionmentioning
confidence: 99%